2003
DOI: 10.1111/j.1752-7325.2003.tb03485.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Examinations Among Adults at High Risk: Findings from the 1998 National Health Interview Survey

Abstract: Objectives: Cigarette smoking and alcohol use are risk factors for oral and pharyngeal cancer. Recommendations for periodic oral cancer examinations highlight the importance of examining high‐risk smokers and alcohol users. This investigation assessed whether cigarette smoking and alcohol use were associated with receipt of an oral cancer examination. Methods: The cross‐sectional 1998 National Health Interview Survey was used. Covariates included age, sex, race/ethnicity, poverty status, and geographic region.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 29 publications
2
20
0
1
Order By: Relevance
“…The purpose of this report was to expand upon previous analyses of national OCE data. Upon comparing our findings with analyses of NHIS data from 1992 and 1998 , it would appear that OCE rates have increased over time for adults aged 40 years or older. Considering examinations conducted solely at the intraoral palpation site, OCE rates have risen from 15 percent to 20 percent to 27 percent over that time frame.…”
Section: Discussionmentioning
confidence: 76%
“…The purpose of this report was to expand upon previous analyses of national OCE data. Upon comparing our findings with analyses of NHIS data from 1992 and 1998 , it would appear that OCE rates have increased over time for adults aged 40 years or older. Considering examinations conducted solely at the intraoral palpation site, OCE rates have risen from 15 percent to 20 percent to 27 percent over that time frame.…”
Section: Discussionmentioning
confidence: 76%
“…Healthy People 2020 review, managed by the US Department of Health and Human Services, set goals to increase the number of adults with an annual oral cancer screening and the proportion of oral cancer diagnosed at the local stage from 23% to 29% [115]. Despite these recommendations, only 15%-19% of adults aged 40 years report receipt of an oral cancer examination in their lifetime [116][117][118]. There is currently no standard or routine screening test to diagnose lip, oral cavity, and pharyngeal cancers, and no screening guidelines have been provided for the early detection of lip, oral cavity, and pharyngeal leukoplakia and erythroplakia lesions or cancers in the general population.…”
Section: Screening Approachesmentioning
confidence: 99%
“…The lack of HNC screening consensus is due to the paucity of well-designed, randomized prospective trials. The US Preventive Services Task Force has concluded that current evidence is insufficient to assess the balance of benefits versus harms of oral cancer screening in asymptomatic adults [116].…”
Section: Screening Approachesmentioning
confidence: 99%
“…Using data from the 1998 NHIS, Macek et al . demonstrated that current smokers were not more or less likely to have received an OCS exam than never smokers. Reporting on a population‐based statewide telephone survey in Florida from 2002, Tomar and Logan found just 19.5 percent of adults reported receiving an oral cancer examination in the previous year, with this percentage being statistically significantly lower among current smokers.…”
Section: Discussionmentioning
confidence: 93%